2018
DOI: 10.21580/vjv7i12735
|View full text |Cite
|
Sign up to set email alerts
|

Teacher’s Directive Speech Acts at Kindergarten School

Abstract: The research is field research with descriptive qualitative research. The research aims to determine and investigate the teacher's directive speech acts at kindergarten school. The research investigates a teacher in a day of teaching-learning activity at kindergartenschool. Deeply, the research investigates a whole sequence of activity in the class. Actually, there are 6 sessions of the learning activity determined such as; 1) forming in line, 2) circle time, 3) praying up, 4) learning activity, 5) take a rest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Then, findings related to using speech-asking students were also found in previous studies. However, this research was conducted with teachers for low-grade students, such as elementary and Female EFL Preservice Teacher Speech Acts Used in Classroom Interaction Isli Iriani Indiah Pane, Arbain kindergarten (Nisa & Abduh, 2022;Sari, 2018). These speeches aim to increase the effectiveness of teaching and learning, making students active in class so students can focus on learning.…”
Section: Discussionmentioning
confidence: 99%
“…Then, findings related to using speech-asking students were also found in previous studies. However, this research was conducted with teachers for low-grade students, such as elementary and Female EFL Preservice Teacher Speech Acts Used in Classroom Interaction Isli Iriani Indiah Pane, Arbain kindergarten (Nisa & Abduh, 2022;Sari, 2018). These speeches aim to increase the effectiveness of teaching and learning, making students active in class so students can focus on learning.…”
Section: Discussionmentioning
confidence: 99%
“…A research conducted by Putri (2015) that the result found function of teachers' directives speech acts were perform a specific action, to assess students' information about a specific task, to request permission, and to direct students' attention during the teaching-learning process. Also, it answered the study conducted by Sari (2018) where requests, requirements, and questions are three sorts of directive speech acts that are frequently employed by teachers. Furthermore, Etikasari (2012) revealed order, requirements, requestives, invitation, prohibitives, suggestion, and persuasion are found in the introduction activity, core, and closing.…”
Section: Ds-5/t1/m-3/067 Finish Ya the First Paragraph Then The Secon...mentioning
confidence: 99%
“…The teachers' more creativities internally caused the teachers' dominance in the Christian and state kindergartens in teaching, which require the students' involvement in the activities. Naturally, the teaching-learning process in a kindergarten class is noisy (Sari, 2018). It implies that the teachers have to show direct, strong, and seemingly rude commands so that the class is conducive to learning.…”
Section: Factors Influencing the Politeness Of Dsa Based On The Schools' Missionsmentioning
confidence: 99%
“…On the other hand, there were limited studies on DSA conducted in kindergartens in which students were taught in parenting framework. Among others were the ones conducted by Ratmaningsih (2013), Rachman (2015), Sari (2018), Anjani & Sri Dewi (2019), Swari et al (2020), Hermawan & Hadi (2021), and Rismayutinna (2021.…”
Section: Introductionmentioning
confidence: 99%